Improved Pain and Function in Knee Osteoarthritis with Dexamethasone Phonophoresis: A Randomized Controlled Trial - Said Ahmed, Mohamed Ahmed (Indian J Orthop, 2019)
BACKGROUND: Intraarticular corticosteroid injection is an adjunct to core treatments for relief of moderate-to-severe pain in osteoarthritis (OA) patients. This randomized controlled trial was conducted to determine the effect of dexamethasone phonophoresis (DxPh) on knee OA. PATIENTS AND METHODS: Forty six female patients with knee OA were randomized into two equal groups. The study group received DxPh over the medial side of the knee, transcutaneous electrical nerve stimulation (TENS), and quadriceps strengthening exercises. Control group received ultrasound therapy and the same TENS and exercise program. Pain was assessed using the visual analog scale (VAS) and the pain subscale of Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pre- and posttreatment. Functional mobility was assessed by the Timed Up and Go (TUG) test, total WOMAC, and the joint stiffness and physical function subscales of WOMAC. The minimal clinically identifiable difference was used to calculate treatment effect sizes of both modalities, which was compared to intraarticular steroid injections. RESULTS: The VAS, TUG, and WOMAC scores improved with both modalities. Pain intensity improved by 50.6%–58.0% in the study group (VAS and pain subscale of WOMAC, respectively) compared to 17.8%–28.6% for the control group. Functional mobility showed a higher rate of improvement in the DxPh group compared to control (37.7 vs. 17.5% for TUG and 53.2 vs. 23.0 and 56.1 vs. 26.4% for the joint stiffness and physical function subscales of WOMAC, respectively). Posttreatment results revealed statistically and clinically significant improvement in pain intensity and functional mobility in the DxPh group. CONCLUSION: DxPh resulted in a greater improvement in pain and function in patients with knee OA than therapeutic ultrasound combined with exercise and TENS. The effect size of phonophoresis was clinically significant and higher than that reported for intraarticular steroid injection from pooled data in the literature.